ANALYSIS OF COGNITIVE ABILITIES OF 5TH GRADE ELEMENTARY SCHOOL STUDENTS IN DOING SCHOOL ASSIGNMENTS USING GOOGLE FORM APPLICATION - Dhea Juliana; Indhira Asih Vivi Yandari; Trian Pamungkas Alamsyah (JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
AbstractThis research aims to analyze the cognitive abilities of 5th  grade elementary school students in doing school assignments using the Google Form application. This research was conducted at SD Negeri Simpang Tiga Cilegon in the academic year of 2020/2021. This research uses a qualitative approach with the triangulation method. In this research, the triangulation used is the triangulation of data sources and the triangulation of theory. After the data is complete, then it is validated from various sources so it can be the basis for drawing conclusions. The instruments used are the teacher interview instruments, teacher observations instruments, and teacher interview and observations instruments.In this research, it was found that students in the level of remembering (C1) obtained 54.50% on the quiz results which include the medium category. The level of understanding (C2) obtains 79.38% on the quiz results that include the high category. The application level (C3) obtains a score of 0 because the results of the quiz scores are the same as the results of the evaluation scores. On the analysing level (C4) the quiz results obtain a score of -42.93% for negative results because the quiz score is bigger than the evaluation score of the analysing level. On the evaluation level (C5) the quiz results obtain a score of -70.67% for negative results because the quiz scores are bigger than the evaluation score of the evaluation level. In the creating level (C6) the quiz results obtain a score of 48.89% which includes the medium category. The results of the research conclude that studying from home during the Covid-19 pandemic can improve students’ cognitive abilities by using the Google Form application.Keywords: Cognitive Ability, Google Form Application